Hepatitis D Virus Status Among People With Hepatitis B Virus Infection: A Disconnect Between Guidelines and Practice - Kathryn Jack; Rachel Jackson; William Lucien Irving (GastroHep)
Conclusion: Some clinicians lack familiarity with clinical guideline recommendations for universal testing of all HBsAg-positive patients. Similarly, most patients lack knowledge about HDV. Staff and patient education are required to increase HDV diagnosis.